2015
DOI: 10.1039/c5ra10204a
|View full text |Cite
|
Sign up to set email alerts
|

Chelate N,O-palladium(ii) complexes: synthesis, characterization and biological activity

Abstract: ARTICLE This journal isThe four trans chelate N, O-palladium(II) complexes were synthetized starting from salicylaldehyde anil Schiff bases, as ligands. Their structure was elucidated using experimental and theoretical tools. The structures of the theoretically possible cis isomers are examined using DFT method. The biological activity, in vitro cytotoxic and prooxidative effects against human breast carcinoma MDA-MB-231, human colon carcinoma HCT-116, and human fibroblast healthy MRC-5 cell lines of investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 40 publications
2
13
0
Order By: Relevance
“…Notably, when the reaction was performed in the absence of pd‐catalyst ( Z 4 ), no formation of product coupled product (1) was observed (Table S1, entry 9 ). Meanwhile, Pd (OAc) 2 , PdCl 2 (PPh 3 ) 2 and pd‐catalyst ( Z 6 ) (see SI Scheme S 2 ) as comparative catalysts gave a very poor yield forming product coupled product (1) under optimal conditions (Table S1, entries 23, 24, 25 ), and the structure of pd‐catalyst ( Z 6 ) was confirmed according to HR‐MS and FT‐IR Spectroscopy analysis (See SI , ). This might be due to the steric environment adjacent to the nitrogen atom of the ligand ( Z 3 ) enhanced the thermal stability of the palladium species.…”
Section: Resultsmentioning
confidence: 92%
“…Notably, when the reaction was performed in the absence of pd‐catalyst ( Z 4 ), no formation of product coupled product (1) was observed (Table S1, entry 9 ). Meanwhile, Pd (OAc) 2 , PdCl 2 (PPh 3 ) 2 and pd‐catalyst ( Z 6 ) (see SI Scheme S 2 ) as comparative catalysts gave a very poor yield forming product coupled product (1) under optimal conditions (Table S1, entries 23, 24, 25 ), and the structure of pd‐catalyst ( Z 6 ) was confirmed according to HR‐MS and FT‐IR Spectroscopy analysis (See SI , ). This might be due to the steric environment adjacent to the nitrogen atom of the ligand ( Z 3 ) enhanced the thermal stability of the palladium species.…”
Section: Resultsmentioning
confidence: 92%
“…Redox parameters: superoxide anion radical determined by NBT (Auclair and Voisin 1985), nitrites by Griess (Griess 1879) and glutathione by GSH assay (Baker et al 1990). For investigation of influence of tested substances on cell viability and redox status we used standardized procedures briefly described in our previous papers (Kosaric et al 2014;Petrovic et al 2014Petrovic et al , 2015. For the purposes of redox status assays we used concentrations of 1, 10, 50 and 100 μM, while IC 50 values are determined as a plot of % cytotoxicity versus sample concentrations.…”
Section: Determination Of Cell Viability and Redox Status Parametersmentioning
confidence: 99%
“…We found that Pd(II) exerted the most significant cytotoxic effect with very low IC 50 values (39.1 and 1.3 µM for 24 h and 72 h after treatment). Such a denominated cytotoxic character could be compared to the effect of the most cytotoxic substances, e.g., cisplatin, which under our laboratory conditions showed lower cytotoxic effects on HCT-116 cells with IC 50 values of 255 and 29 µM measured 24 and 72 h after treatment (Petrovic et al, 2015).…”
Section: Biological Evaluation 321 Cytotoxicity Of Rh(iii) Pt(iv)mentioning
confidence: 99%
“…Recently we showed that the choosing of appropriate ligands could provide palladium(II) complexes that are extremely cytotoxic to cancer cells (Petrovic et al, 2015). Under standard laboratory conditions for in vitro testing, it was shown that those Pd(II) complexes produced extremely high levels of reactive radical species and that could be toxic to cancer cells, even more so than cisplatin.…”
Section: Introductionmentioning
confidence: 99%